2018
DOI: 10.1155/2018/6421243
|View full text |Cite
|
Sign up to set email alerts
|

Adult Height after Growth Hormone Treatment at Pubertal Onset in Short Adolescents Born Small for Gestational Age: Results from a Belgian Registry-Based Study

Abstract: Objectives Information on the efficacy of GH treatment in short SGA children starting their treatment in adolescence is limited. Therefore, adult height (AH), total height gain, and pubertal height gain were evaluated in short SGA children who started GH treatment at pubertal onset. Patient and Methods Growth data of 47 short SGA adolescents (22 boys) who started GH treatment at pubertal onset (PUB group) were compared with results from 27 short SGA patients (11 boys) who started GH therapy at least 1 year bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
2
10
1
8
Order By: Relevance
“…However, other studies, such as that of Beisti, 16 found a smaller difference in genetic height as a factor associated with AH gain. The difference between the sexes observed in our study in terms of HG is not described in the literature; in fact, in the Belgian study, 18 a lower AH and HG was observed in girls compared with boys. This last study showed a positive correlation between AH and height at the beginning of treatment, a result similar to that obtained in our sample.…”
Section: Discussioncontrasting
confidence: 89%
“…However, other studies, such as that of Beisti, 16 found a smaller difference in genetic height as a factor associated with AH gain. The difference between the sexes observed in our study in terms of HG is not described in the literature; in fact, in the Belgian study, 18 a lower AH and HG was observed in girls compared with boys. This last study showed a positive correlation between AH and height at the beginning of treatment, a result similar to that obtained in our sample.…”
Section: Discussioncontrasting
confidence: 89%
“…Consistent with these studies, we found an average height gain of 0.7 SD (±1.0) in treated SGA children. In addition, we were able to confirm that rhGH treatment allowed SGA children to reach a final height of between −0.9 and −2.1 SD, that is, within the normal range for the majority of patients [15-17, 21, 31, 32]. Mairoara and Cianfarani [33] in 2009 reported a meta-analysis including 29 studies showing the efficacy of rhGH for improving adult height.…”
Section: Discussionmentioning
confidence: 63%
“…Better response is seen when GH is initiated pre-pubertally. 1,[4][5][6]30 Thus, the full pattern of catch-up growth could not be fully assessed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3] Treatment is aimed to improve linear growth, metabolic parameters, and adult height; outcomes are improved by early start and long treatment duration. [4][5][6][7] Motivation for long-term commitment to regular injections by patients and/or caregivers may decrease over time as continuous daily subcutaneous injections may be perceived to be burdensome, with less obvious treatment benefits. [8][9][10][11] Poor adherence to GH therapy is reported to be common, with consequent decrease in efficacy outcomes.…”
mentioning
confidence: 99%